Rātchaphat wičhai phūa kāns̄œmsāng khwāmkhemkh̄æng kh̨̄ong chumchon (Samnakngān Saphā Sathāban Rātchaphat : Sathāban Rātchaphat Phibūn Songkhrām Čhangwat Phitsanulōk, 2001)
Research abstracts of educators at Rajabhat Institute Pibulsongkram, Thailand, 2001.